Uma metodologia simplificada de estimaç\~ao da carga tributária líquida brasileira trimestral no período 1995-2007 - Cláudio H. dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This paper presents a simplified methodology for estimating quarterly figures for both the Brazilian government transfers and net aggregate tax burden in the 1995-2007 years. It also describes the main stylized facts observed in the data in this period, calling attention to the fact that Brazilian government transfers apparently have become more progressive in recent years.
Keywords: C82; E01; H53; 330; Öffentliche Sozialleistungen; Steuerbelastung; Brasilien